Occurrence of aflatoxin M1 in raw milk traded in peri-urban Nairobi, and the effect of boiling and fermentation - Kuboka, M.M.; Imungi, J.K.; Njue, L.; Mutua, Florence K.; Grace, Delia; Lindahl, Johanna F. (Informa UK Limited, 2019)
Background: Dairy production in Kenya is important and dominated by small-holder farmers who market their produce through small-scale traders in the informal sector. Method: This study aimed to determine the prevalence of aflatoxin (AFM1) in informally marketed milk in peri-urban Nairobi, Kenya, and to assess knowledge of milk traders on aflatoxins using questionnaires. A total of 96 samples were analyzed for AFM1 using enzyme-linked immunosorbent assay. In addition, boiling and fermentation experiments were carried out in the laboratory. Results: All samples had AFM1 above the limit of detection (5 ng/kg) (mean of 290.3 ± 663.4 ng/kg). Two-thirds of the samples had AFM1 levels above 50 ng/kg and 7.5% of the samples exceeded 500 ng/kg. Most of the traders had low (69.8%) or medium (30.2%) knowledge. Educated (p = 0.01) and female traders (p= 0.04) were more knowledgeable. Experimentally, fermenting milk to lala (a traditional fermented drink) and yogurt significantly reduced AFM1 levels (p< 0.01) (71.8% reduction in lala after incubation at room temperature for 15 h, and 73.6% reduction in yogurt after incubation at 45ºC for 4h). Boiling had no effect. Conclusion: The study concluded that the prevalence of raw milk with AFM1 was high, while knowledge was low. Fermentation reduced the AFM1 levels.